Yersinia enterocolitica survival in aquatic environment: epidemiological significance - Ossiprandi, Maria Cristina (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
The survival of four biotypes of Yersinia enterocolitica (2 isolated from swine and 2 from Chironomus larvae) has been assessed in two types of surface water, with low and high content of organic matter, at 3 different temperatures. The results have shown that the bacteria undergo active replication during the first weeks of incubation; thereafter, they can survive up to 74 weeks, with the survival time strongly influenced by the incubation temperature. Therefore, surface waters may be an important reservoir for the biotypes considered and thus, they may play a strategic role in the epidemiology of Yersinia infections.